The Systematic Impact of Personal Characteristics on Entrepreneurial Intentions of Engineering Students - Sun, Hongyi; Ni, Wenbin; Teh, Pei-Lee; Lo, Carol (Frontiers in Psychology, 2020)
The impact of personal characteristics on entrepreneurial intention is a classic topic in the field of entrepreneurship research. Previous research mostly used simple linear models, leading to a gap in the study on the interrelationship among personal characteristics and their systematic influence on entrepreneurial intention. This study investigates the interrelationship among the four specific entrepreneurial characteristics (i.e., need for achievement, locus of control, risk-taking propensity and creativity) and their systematic influence on the entrepreneurial intention of engineering students. The research data is from 210 engineering students via a survey. Logistic regression and path analysis were used for data analysis. The findings suggest that creativity and risk-taking directly influence entrepreneurial intention while the need for achievement and the locus of control influence it indirectly. Implications for entrepreneurship education are finally discussed.